2017
DOI: 10.18203/2320-6012.ijrms20173572
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche and the menstrual pattern of secondary school adolescents in central India

Abstract: Background: Population studies on characteristics of menstrual cycles are scarce. Knowledge on this variability is necessary for patient education and to guide clinical evaluation.Methods: A cross sectional study was conducted and 622 school girls were selected randomly. A pretested questionnaire was used to gather data.Results: Mean age of participants was 16.9 ± 1 years. About 92.2% had attained menarche. Probit analysis of the status-quo data yielded median age at menarche of 14.8 (13.9-15.3) years and by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…3 23,24 Studies have shown optimum 3-5 days of flow is usual among girls and is considered normal besides comprehending above and below this range as heavy and scanty flow respectively. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Consistent with this in present study majority of girls 52.26% had 2-4 days bleeding followed by 5-7 days in 38.68% and small proportion had >8 days (5.4%) and <2 days (3.66%).…”
Section: Figure 4: Cycle Effect Of Menstruation On Daily Routine Of Asupporting
confidence: 83%
See 2 more Smart Citations
“…3 23,24 Studies have shown optimum 3-5 days of flow is usual among girls and is considered normal besides comprehending above and below this range as heavy and scanty flow respectively. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Consistent with this in present study majority of girls 52.26% had 2-4 days bleeding followed by 5-7 days in 38.68% and small proportion had >8 days (5.4%) and <2 days (3.66%).…”
Section: Figure 4: Cycle Effect Of Menstruation On Daily Routine Of Asupporting
confidence: 83%
“…(Figure 4). [10][11][12][13][14][15][16][17][18][19][20] While considerably higher age of menarche has been reported by Kanotra et al in Maharashtra and Indupalli in Karnataka. 21,22 This variation may be due to the recall bias in latter studies as age of study subjects was higher and time between the occurrence of menarche and data collection was protracted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that menarcheal age was delayed and varied by residence. Dysmenorrhea was a prevalent issue in school adolescents causing school absenteeism (16).…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with studies done in Nigeria, Malaysia and in Central India wherein the major source of information was mother. [16][17][18] Attitude of mothers and teachers in discussing the menstruation related issues are barriers to the right kind of information, especially in the rural areas. 19…”
Section: Discussionmentioning
confidence: 99%